Pengaruh Muslim-friendly service design dan memorable experience terhadap loyalitas wisatawan melalui community engagement - Natasya Putri Syahira; Bethani Suryawardani; Alma Syifa (Universitas Widya Mataram, 2026)
This research is motivated by the declining loyalty of Muslim tourists to urban halal tourism destinations despite the increasing number of visits. In addition, the influence of Muslim-Friendly Service Design on loyalty still shows inconsistent results and the role of Muslim Community Engagement as a mediating variable is still limited research. This study aims to analyze the influence of Muslim-Friendly Service Design and memorable experience on Muslim tourist loyalty through Muslim Community Engagement in the Trans Studio Bandung Integrated Area. The study used a quantitative approach with a survey method of 150 respondents and was analyzed using SEM-PLS. The results showed that memorable experience and Muslim Community Engagement have a significant positive effect on Muslim tourist loyalty, while Muslim-Friendly Service Design has no direct effect on loyalty, but has a significant effect on Muslim Community Engagement. These findings indicate that memorable tourism experiences and community involvement play an important role in strengthening Muslim tourist loyalty.